2015
DOI: 10.1182/blood-2014-07-587329
|View full text |Cite
|
Sign up to set email alerts
|

Myxoma virus suppresses proliferation of activated T lymphocytes yet permits oncolytic virus transfer to cancer cells

Abstract: Key Points MYXV binds human T lymphocytes but does not enter and infect T cells until after activation. MYXV-infected T lymphocytes proliferate less and secrete less inflammatory cytokines but deliver oncolytic virus to augment GVM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…However, >95% of all infections that initiate MYXV infection in human hematopoietic cells (i.e., cells that turn green after infection with vMyx-GFP) abort the virus replication cycle prior to the late stage of virus replication, and therefore cannot make progeny virus and are considered functionally nonpermissive for MYXV. Fresh mPBSCs showed slightly higher levels of MYXV infection initiation in differentiated cells like monocytes and NK cells, most likely due to manipulation-induced activation of some differentiated cells, as we have previously shown 15 . When considering our recent report of primary human T lymphocytes serving as transport vehicles for MYXV to target cancer cells 15 , the limited infection found in this study are interpreted as a potentially positive finding in assisting MYXV delivery to cancer cells post-transplant.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…However, >95% of all infections that initiate MYXV infection in human hematopoietic cells (i.e., cells that turn green after infection with vMyx-GFP) abort the virus replication cycle prior to the late stage of virus replication, and therefore cannot make progeny virus and are considered functionally nonpermissive for MYXV. Fresh mPBSCs showed slightly higher levels of MYXV infection initiation in differentiated cells like monocytes and NK cells, most likely due to manipulation-induced activation of some differentiated cells, as we have previously shown 15 . When considering our recent report of primary human T lymphocytes serving as transport vehicles for MYXV to target cancer cells 15 , the limited infection found in this study are interpreted as a potentially positive finding in assisting MYXV delivery to cancer cells post-transplant.…”
Section: Discussionsupporting
confidence: 63%
“…Fresh mPBSCs showed slightly higher levels of MYXV infection initiation in differentiated cells like monocytes and NK cells, most likely due to manipulation-induced activation of some differentiated cells, as we have previously shown 15 . When considering our recent report of primary human T lymphocytes serving as transport vehicles for MYXV to target cancer cells 15 , the limited infection found in this study are interpreted as a potentially positive finding in assisting MYXV delivery to cancer cells post-transplant.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In addition to this, ex vivo virotherapy with MYXV also completely eliminated acute GVHD in this xenotransplanted mouse model by suppressing the subsequent expansion and infiltration of alloreactive human T lymphocytes into normal recipient tissues 16 . Recently, it was shown that normal human T cells can bind MYXV and can then co-traffic with these cells, but the virus infection is launched only after T cell activation 21 . Importantly, activated and/or infected T cells can subsequently donate the oncolytic MYXV to human MM cells via cell-cell contact 21 …”
Section: Introductionmentioning
confidence: 79%